2006
DOI: 10.1111/j.1600-0897.2005.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL‐1, in the Testes of Adult Mice, Following Subcutaneous Administration of Turpentine

Abstract: Our results demonstrate for the first time the distant effect of acute localized inflammation on testicular IL-1 levels. Thus, transient inflammatory response to infectious/inflammatory agents at non-testicular sites that elicit systemic IL-1 response should be considered during clinical treatment as a possible factor of male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It is also interesting to note that IL-1ß levels were found to be reduced in human testicular sections with impaired spermatogenesis [ 47 , 56 ]. It has been suggested that this was somehow related to Leydig cell apoptosis [ 47 , 57 , 58 ]. In this context, homeostasis of the testicular IL-1ß pathway could regulate androgen production and consequently spermatogenesis [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is also interesting to note that IL-1ß levels were found to be reduced in human testicular sections with impaired spermatogenesis [ 47 , 56 ]. It has been suggested that this was somehow related to Leydig cell apoptosis [ 47 , 57 , 58 ]. In this context, homeostasis of the testicular IL-1ß pathway could regulate androgen production and consequently spermatogenesis [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Serum IL-6 and IL-1 are high during this early phase, whereas serum TNFa does not play a role. Five days after turpentine serum IL-1 and IL-6 decrease, temperature and food-intake return to normal and mice recover, although liver Il1b mRNA increases which is characteristic for the development of a systemic acute phase response (Boelen et al 1996, 2005, Leon 2002, Elhija et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the increased expression of these proinflammatory cytokines results in testicular dysfunction [36]. Models of acute inflammation by injection of turpentine [37] and experimental varicocele [38] increased protein or mRNA levels of both IL-1α and IL-1β in the testis. However, the kinetics of testicular IL-1 in EAO have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%